Screening of β-hairpin peptide-engrafted 1, 2, 3-triazoles to identify APEH enzyme inhibitors1. Issue 13 (14th February 2015) - Sandomenico, A.; Celentano, V.; D'Andrea, L. D.; Palmieri, G.; Ruvo, M.
<x xml:space="preserve">Abstract</x> Peptide-engrafted triazoles, obtained via click chemistry, drive the inhibition activity toward Acyl Peptide Hydrolase (APEH), a modulator of the proteasome activity.